Meninjau Kembali Gugatan Feminisme Terhadap Institusi Rumah Tangga dan Dalil Bias Gender dari Perspektif Islam - Qaem Aulasyahied (Universitas Darussalam Gontor, 2019)
This paper discusses the Feminism lawsuit against Household institutions. Feminism from various schools, liberal feminism, radical feminism, and also socialist or Marxist feminism criticized the household which they considered as a form of discrimination against women from the smallest unit. Islam as a religion that advises its adherents to get married and have family, also does not escape the criticism of feminists. At least, there are two aspectsthat are criticized. First, the traditions of Muslim communities in various parts of the world reflecting discriminatory families. Secondly, the creation of the tradition was because some religious propositions became a source of patriarchy views. Islam itself highly upholds justice between men and women. Nor does it deny the existence of differences between the two butthe difference is not to show the superiority of men over women. As for the arguments that are considered gender bias, this is due to understanding the proposition without scientific tools and comprehensive insight. Because if it is well understood, the seemingly misogynistic argument actually contains elements of justice and glorification of women.